1999
DOI: 10.1089/jop.1999.15.455
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis for Pharmacokinetic Studies of Ceftazidime in Rabbit Vitreous

Abstract: The method of microdialysis was used for collecting series of samples from the rabbit vitreous after systemic and intravitreous administration of ceftazidime. The purpose of the study was to compare the method with traditional pharmacokinetic sampling. Ceftazidime was injected intramuscularly (1 mg/kg) or intravitreally (1 mg) in rabbits, with a previously implanted microdialysis probe in the vitreous. The membrane was perfused with a buffer, and the dialysate was collected in samples where the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Microdialysis has served as an important tool in sampling of ocular fl uids both by reducing the number of animals and providing statistically powered data. [41][42][43][44][45][46][47] The main objective of this study was to perform the ocular pharmacokinetics of GCV and its prodrug (Biotin-GCV). The pharmacokinetic studies were done to conclude whether the prodrug had better or if not comparable pharmacokinetic profi les to parent drug.…”
Section: Discussionmentioning
confidence: 99%
“…Microdialysis has served as an important tool in sampling of ocular fl uids both by reducing the number of animals and providing statistically powered data. [41][42][43][44][45][46][47] The main objective of this study was to perform the ocular pharmacokinetics of GCV and its prodrug (Biotin-GCV). The pharmacokinetic studies were done to conclude whether the prodrug had better or if not comparable pharmacokinetic profi les to parent drug.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the problem of BBB penetration, it was shown for the eye (176) that the penetration of ceftazidime into the vitreous after intramuscular injection was ϳ50% higher in inflamed than in noninflamed eyes, suggesting interference with the blood-retina barrier (177). The problem of transport across the blood-retina barrier is particularly important for the treatment of cytomegalovirus retinitis.…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 97%
“…[18][19][20][21][22] Moreover, conscious animal model for ocular microdialysis has already been developed and validated. 17,[23][24][25][26][27] Studies from our laboratory have demonstrated the effect of probe implantation in the rabbit eye on vitreal protein levels and pharmacokinetics. 17,23 The studies have also validated the method of such probe implantation and recommended that the appropriate recovery time must be allowed before commencing any pharmacokinetic study in conscious animal model.…”
Section: Introductionmentioning
confidence: 99%